1995
DOI: 10.1523/jneurosci.15-06-04572.1995
|View full text |Cite
|
Sign up to set email alerts
|

Kinase and phosphatase activities intimately associated with a reconstituted calcium-dependent potassium channel

Abstract: Type-2 calcium-dependent potassium (KCa) channels from mammalian brain, reconstituted into planar phospholipid bilayers, are modulated by ATP or ATP analogs via an endogenous protein kinase activity intimately associated with the channel (Chung et al., 1991). We show here that the endogenous protein kinase activity is protein kinase C (PKC)-like because (1) modulation by ATP can be mimicked by exogenous PKC, and (2) the effects of ATP can be blocked by PKC(19-36), a specific peptide inhibitor of PKC. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 28 publications
8
83
0
Order By: Relevance
“…In these assays we stimulated PKA activity intimately associated with the channel by applying cAMP to the intracellular face of isolated inside-out patches. As previously reported (17) the effects of cAMP in this system are dependent upon the presence of Mg-ATP, and the actions of cAMP are completely abolished by the PKA inhibitor peptide PKI [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . Although STREX channels are inhibited whereas ZERO channels are activated by PKA closely associated with the channel (17), the short LZ1-competing peptides effectively blocked PKAdependent regulation of either splice variant.…”
Section: Pkac Docking With Mouse Bk Channel Variants Mediated Via a Lz1supporting
confidence: 80%
“…In these assays we stimulated PKA activity intimately associated with the channel by applying cAMP to the intracellular face of isolated inside-out patches. As previously reported (17) the effects of cAMP in this system are dependent upon the presence of Mg-ATP, and the actions of cAMP are completely abolished by the PKA inhibitor peptide PKI [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . Although STREX channels are inhibited whereas ZERO channels are activated by PKA closely associated with the channel (17), the short LZ1-competing peptides effectively blocked PKAdependent regulation of either splice variant.…”
Section: Pkac Docking With Mouse Bk Channel Variants Mediated Via a Lz1supporting
confidence: 80%
“…Dephosphorylation of presumably Ser 1151 , by pretreating inside-out patches from TSMCs with ATP-free solution in the presence of the PKC pseudosubstrate inhibitor PKC [19][20][21][22][23][24][25][26][27][28][29][30][31] , resulted in a switch of channel regulation from PKG to PKA, resembling the switch in the S 1151 A mutant. The regulation of BK channels by closely associated phosphatases has been shown before (16)(17)(18). Therefore, the switch of channel regulation from PKG to PKA was likely due to the activity of a phosphatase that had dephosphorylated the channel at the PKC motif before the channel became responsive to PKA.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we wondered whether the effect of CCh on BK channel activity can be mimicked by the inhibition of channel-associated protein phosphatases (16)(17)(18). When we superfused inside-out patches from TSMCs with 20 nM of the protein phosphatase 1 inhibitor peptide (PPI2) for 5 min, NP o decreased by ∼50% at all (Fig.…”
Section: Pkc-dependent Inhibition Of Bk Channels In Tracheal Smooth Mmentioning
confidence: 99%
“…When phosphatase activity was inhibited by microcystin, the mean current passed through the K-ATP channel in a single inside-out patch was approximately doubled. It is reported that microcystin can also enhance the modulation of K-Ca channel activity by ATP (Reinhart and Levitan 1995).…”
Section: Neurochannelmentioning
confidence: 99%